From pathogenesis to personalized treatments of neuropathies in hematological malignancies. Issue 3 (7th August 2020) - Briani, Chiara; Visentin, Andrea; Cerri, Federica; Quattrini, Angelo
Abstract: The peripheral nervous system may be involved at any stage in the course of several hematological diseases, the most common being monoclonal gammopathies (of undetermined significance or malignant) or lymphomas. The underlying pathogenic mechanisms are different and therapies aim at targeting the dangerous either B‐cell or plasma cell clones. Recently, high‐throughput technologies, and next‐generation sequencing have increased our knowledge of hematological diseases pathogenesis by the identification of somatic mutation affecting pivotal signaling pathways. Accordingly, new target therapies are used that may also be borrowed for treatment of neuropathies in hematological diseases.